Case Report: Immune checkpoint inhibitor-induced myositis without elevated creatine kinase - Begaj, Klajdi; Wilhelm, Raphael; Lepper, Alisa; Kaufhold, Maike; Veeser, Jakob; Grabbe, Stephan; Stege, Henner (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of advanced cancers like malignant melanoma. However, they can lead to a range of immune-related adverse events (irAEs), impacting various organ systems. Among these, myositis is a rare but serious irAE, typically characterized by myalgia, muscle weakness, and elevated creatine kinase (CK) levels. Herein, we report the case of a 58-year-old female with advanced melanoma, who presented a delayed-onset of ICI-induced myositis accompanied by severe muscle weakness. Interestingly, the CK levels remained normal throughout her disease course. Neurological examination, MRI, and electromyography were pivotal in diagnosing myositis. Differential diagnoses, including myasthenia gravis, myocarditis, and paraneoplastic syndromes or idiopathic inflammatory myopathies, were systematically ruled out through clinical evaluation, serological testing, and imaging. The patient responded favorably to high-dose corticosteroid therapy, leading to a gradual improvement of symptoms and no relapse after stopping treatment. This case report emphasizes a multimodal diagnostic approach and underscores the importance of clinical awareness for such atypical irAE presentations.